The Effect of Camshaft Modification on Fuel Consumption and AFR Value on The Honda Supra X 125 Motorcycle - Wahyu Hidayat; Abdurrahman; Ranu Iskandar; Rizqi Fitri Naryanto (Universitas Negeri Semarang, 2026)
This study investigated the effects of camshaft modification and fuel variation on fuel consumption and air–fuel ratio (AFR) in a Honda Supra X 125 motorcycle. An experimental design was employed using three camshaft configurations standard, touring, and racing and two fuels: pure Pertamax and Pertamax blended with an octane booster. Fuel consumption was measured at idle and 5000 rpm based on the time required to consume 20 mL of fuel, while AFR was measured under idle conditions. Each test was repeated three times, and the results were expressed as mean ± standard deviation. At idle, the standard camshaft produced the longest fuel-consumption time, reaching 8.14 ± 0.09 min/20 mL with pure Pertamax and 9.22 ± 0.06 min/20 mL with the blended fuel. At 5000 rpm, the touring camshaft with the blended fuel produced the longest consumption time at 3.20 ± 0.05 min/20 mL. The racing camshaft consumed fuel more rapidly, with the lowest idle value of 6.57 ± 0.35 min/20 mL using pure Pertamax. AFR values decreased from 14.02 ± 0.06 for the standard camshaft with pure Pertamax to 13.45 ± 0.06 for the racing camshaft with the blended fuel. These findings indicate that camshaft geometry and fuel composition influence fuel-consumption characteristics and mixture richness. The standard camshaft was most efficient at idle, the touring camshaft performed best at 5000 rpm, and the racing camshaft produced the richest mixture.